Características corporais, adiposidade, morfometria radiológica do casco e avaliação radiográfica e ultrassonográfica do boleto de equinos Mangalarga Marchador de alto desempenho - Jéssica Fontana de Magalhães (2022)
The objective was to evaluate the prevalence of alterations in the positioning of the distal phalanx and lesions of the joint and the suspensory ligament of the fetlock (LSB) and their correlations and associations with body characteristics, degrees of adiposity and morphometric variables of the hoof of Mangalarga Marchador (MM) horses. ) high performance. To this end, information was collected on body characteristics, adiposity, radiological morphometry of the hoof and radiographic evaluation of the metacarpophalangeal joint and ultrasound of the LSB of horses presented at national MM exhibitions in 2011, 2017 and 2018. The vast majority of animals presented signs of excessive adiposity (82%) and excessive deposition of adipose tissue in the crest region of the neck (89.74%), characteristics historically related to developmental diseases, insulin dysregulation and laminitis. The majority also presented thoracic hooves with long pincers, excessively dorsal load-bearing, podophalangeal axis broken backwards and drained heels. Several lesions were detected in the joint and in the LSB, with a marked prevalence of dilation of canaliculi (78%) and irregularities in the edges of the proximal sesamoids (72.2%), lesions in the branches (82.8%) and in the origin (44, 9%) of the suspensory ligament of the fetlock and dorsal osteophytes in the proximal phalanx (47.7%), consistent with sesamoiditis, proximal and branch desmitis and osteoarthritis, respectively. Comparing the variables, there was a correlation and association of increased adiposity with greater distance between the horny case and distal phalanx and greater intensity of the presence of osteophytes in the fetlock joint. MM horses with evident cervical adiposity had 1.4 times more prevalence (P=0.008) of distal phalanx sinking and 1.6 times more (P=0.002) of osteophytes in the fetlock. Similar relationships were found between hoof distortions consistent with the practice of leaving the gripper long and injuries to the LSB. MM horses with drained heels had a 1.6-fold greater prevalence of proximal desmitis (P=0.001) and those with a broken back podophalangeal axis had a 1.9-fold greater prevalence of severe desmitis of the medial branch of the suspensory fetlock (P=0.005) . Between the years 2011 and 2017/2018, although there was no reduction in adiposity levels, there was a reduction in the measures of laminitis indicator variables and an improvement in some parameters of hoof conformation, indicating an improvement in trimming and shoeing. These findings support the hypothesis that obesity and inappropriate trimming and shoeing practices promote changes consistent with the development of endocrinopathic laminitis, distortions of the hoof horny and trauma to the joint and suspensory ligament of the fetlock, this set being lesions of high potential to prevent any type of athletic activity and significantly compromise health and well-being in high-performance MM horses.